APPLICATION DEVELOPMENT OF AUGMENTED REALITY FOR ELEMENTARY ENGLISH TEACHING - Irsyad - Nugraha (University of Kuningan, 2023)
When children learn English, they have a limited capacity for long-term attention, which necessitates learning English to be more creative, interactive, and innovative. Furthermore, smartphone technology provides these advantages, one of which is the augmented reality application, a novel issue in English teaching. The purpose of this research is to explain how to design Augmented Reality applications. The research design is the multimedia development life cycle (MDLC), and the research method is descriptive qualitative. It was explained that the augmented reality application could be used with the image distance and the augmented display up to 30 cm and that it could be used by teachers without the assistance of a computer technician using the six cycles of MDLC: concept, design, collecting material, assembly, testing, and distribution. The findings show that Augmented Reality can be used as a creative, interactive, and innovative media to help students learn English.Keywords: Augmented Reality; elementary school; English teaching process.